1996
DOI: 10.1038/hdy.1996.161
|View full text |Cite
|
Sign up to set email alerts
|

The successful founder: genetics of introduced Carduelis chloris (greenfinch) populations in New Zealand

Abstract: The amount and distribution of genetic variation in seven introduced New Zealand populations of Carduelis chioris were assessed at 40 loci using starch gel electrophoresis and compared with those in native European populations. Fewer alleles (1.45) and fewer polymorphic foci (33 per cent) were detected across the introduced populations than across native populations (1.75, 55 per cent), reflecting the narrow geographical origin of the introduced populations. There was no evidence for severe inbreeding or genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…Moreover, the genetic variability is signi cantly lower in the contemporary Scandinavian wolf population than in the eastern or historical wolves (table 2; Wilcoxon's signed rank test for the expected heterozygosity and number of alleles, p , 0.05 in both cases). Low genetic diversity and strong differentiation are consistent with a very small number of individuals founding the Scandinavian population and stress the in uence of genetic drift (Barton & Charlesworth 1984;Merilä et al 1996;Tarr et al 1998). The founding effect may have formed, in just 15 years, a population that is highly differentiated from the source population.…”
Section: (B) Loss Of Genetic Diversitymentioning
confidence: 69%
“…Moreover, the genetic variability is signi cantly lower in the contemporary Scandinavian wolf population than in the eastern or historical wolves (table 2; Wilcoxon's signed rank test for the expected heterozygosity and number of alleles, p , 0.05 in both cases). Low genetic diversity and strong differentiation are consistent with a very small number of individuals founding the Scandinavian population and stress the in uence of genetic drift (Barton & Charlesworth 1984;Merilä et al 1996;Tarr et al 1998). The founding effect may have formed, in just 15 years, a population that is highly differentiated from the source population.…”
Section: (B) Loss Of Genetic Diversitymentioning
confidence: 69%
“…The loss of genetic variation could be extremely rapid throughout the genome in small or localized populations founded by a few individuals and cut off from gene exchange with the main body of the species (Planes and Lecaillon, 1998). In a review of studies of introduced birds, Merilä et al (1996) noted that reductions in genetic diversity tended to be inversely correlated with the number of individuals released. Thus, according to our results, it seems likely that Irish white-clawed crayfish are derived from a low number of introduced individuals translocated from populations in western France.…”
Section: Discussion Origin Of Crayfish In Irelandmentioning
confidence: 99%
“…3). A review of genetic variation in introduced bird species between their native and introduced ranges (including five species from New Zealand) found that more severe bottlenecks indeed reduced genetic variability in the resulting populations (34). Further genetic studies are required to confirm this pattern in both the native and introduced species in this study, but our results suggest that severe bottlenecks result in measurable fitness costs and that this result is consistent with that expected by increased inbreeding and the loss of genetic diversity when populations drop to small numbers.…”
Section: Resultsmentioning
confidence: 99%